Peranan Intelkam Kepolisian Republik Indonesia dalam Kitab Undang - Undang Hukum Pidana Baru - Aditya Wahyudi; Arya Bodhi Kumara; Fakhri Akbar Pranggabaya (CV Edujavare Publishing, 2025)
Security Intelligence (Intelkam) of the Republic of Indonesia Police has a strategic role in maintaining national security stability, including in the context of criminal law enforcement. With the enactment of the new Criminal Code (KUHP), there are various substantial updates that affect the pattern and approach of law enforcement. This research aims to analyze the role of Intelkam in supporting the implementation of the new Criminal Code, especially in terms of early detection of potential security disruptions, intelligence data collection, and coordination with other police functions. The method used is a normative juridical approach with qualitative analysis of regulation and secondary data. The research results show that Intelkam plays an important role in providing strategic input to criminal investigators, mapping potential threats to the implementation of certain articles in the new Criminal Code, and maintaining a balance between civil liberties and public order. Therefore, strengthening the capacity and regulation that supports the Intelkam function is the key to optimizing the implementation of the new Criminal Code in Indonesia.